The Allstons of Chicora Wood : Wealth, Honor, and Gentility in the South Carolina Lowcountry - Scarborough, William Kauffman (Book collections on Project MUSE., 2011)
William Kauffman Scarboroughs absorbing biography, The Allstons of Chicora Wood, chronicles the history of a South Carolina planter family from the opulent antebellum years through the trauma of the Civil War and postwar period. Scarboroughs examination of this extraordinarily enterprising family focuses on patriarch Robert R.F.W. Allston, his wife Adele Petigru Allston, and their daughter Elizabeth Allston Pringle Scarborough.